Vegetarian and Vegan Diet in Fibromyalgia: A Systematic Review - Yolanda Nadal-Nicolás (International Journal of Environmental Research and Public Health, 2021)
Fibromyalgia (FM) is a chronic non-degenerative disease characterized by the presence of multiple symptoms such as chronic pain, which negatively influence the quality of life of sufferers, most of whom are women. Currently, there is no effective treatment to limit the impact of these symptoms. The aim of this research is to review the scientific evidence on the effect of following a vegetarian or vegan diet on fibromyalgia patients. A systematic review included the original articles that answered the research question. These articles were in 2021 in the PubMed, Web of Science and Scopus databases. The research used the PRISMA (preferred reporting items for systematic reviews and meta-analyses) guidelines. No time restriction was applied, and grey literature was not included. The evaluation of the methodological quality of the articles was carried out using the following different scales: STROBE (strengthening the reporting of observational studies in epidemiology), PEDro (Physiotherapy Evidence Database), and MMAT (Mixed Methods Appraisal Tool) scales. A total of 88 studies were analyzed, of which 6 investigations were included in this systematic review (n = 4 clinical trials and n = 2 cohort studies). These investigations show significant improvements in biochemical parameters, quality of life, quality of sleep, pain at rest and general health status when following mainly plant-based dietary patterns. In conclusion, these findings are promising but interpretation of the findings is limited due to the methodological quality of the studies. Well-designed clinical trials are needed to consolidate these dietary recommendations in FM patients.